Biomolecular modelling and simulations - Karabencheva-Christova, Tatyana (Advances in protein chemistry and structural biology, 2014)
Published continuously since 1944, the Advances in Protein Chemistry and Structural Biology series is the essential resource for protein chemists. Each volume brings forth new information about protocols and analysis of proteins. Each thematically organized volume is guest edited by leading experts in a broad range of protein-related topics. Describes advances in biomolecular modelling and simulations Chapters are written by authorities in their field Targeted to a wide audience of researchers, specialists, and students The information provided i.